Predictive Regulatory Change Impact Model for Global Payment Disruption Scenarios - Babajide Oluwaseun Olaogun; Adaobu Amini-Philips; Ayomide Kashim Ibrahim (International Journal of Scientific Research in Humanities and Social Sciences, 2024)
The global payments ecosystem faces unprecedented disruption from technological innovation, geopolitical tensions, and evolving regulatory frameworks that challenge traditional financial infrastructure. This study develops a comprehensive predictive regulatory change impact model specifically designed to assess and forecast the effects of regulatory modifications on global payment disruption scenarios. The research employs a mixed-methods approach combining quantitative modeling techniques with qualitative regulatory analysis to create a robust framework for understanding how regulatory changes propagate through interconnected payment networks. The model integrates machine learning algorithms with regulatory signal detection mechanisms to provide early warning systems for payment system operators, financial institutions, and policymakers. Through extensive analysis of regulatory patterns across major financial jurisdictions including the United States, European Union, United Kingdom, and emerging markets, this research identifies key regulatory drivers that significantly impact payment system stability and innovation trajectories. The study examines how regulatory harmonization efforts, cross-border compliance requirements, and emerging technology governance frameworks influence payment disruption scenarios. The predictive model incorporates variables such as regulatory complexity indices, compliance cost projections, implementation timelines, and market adaptation capacity to generate comprehensive impact assessments. Findings reveal that regulatory changes in core financial hubs create cascading effects across global payment networks, with particularly pronounced impacts on cross-border transactions, digital currency adoption, and fintech innovation ecosystems. The model demonstrates significant predictive accuracy in forecasting regulatory impact scenarios, achieving correlation coefficients above 0.85 in validation testing across multiple jurisdictions and time periods. Practical applications include strategic planning for financial institutions, risk management optimization, and policy development support for regulatory authorities. The research contributes to the growing body of knowledge on regulatory technology applications in financial services while providing actionable insights for stakeholders navigating the complex intersection of regulation and payment system evolution. The study concludes with recommendations for adaptive regulatory frameworks that balance innovation promotion with systemic risk mitigation in an increasingly interconnected global payments landscape.